Poetical Expression of the Essence of Man and the Universe in the Prose of Asad Dilmurad - Nilufar DILMURODOVA (Genius Journals, 2023)
The article examines the problem of poetic expression of the essence of man and the universe in the prose of the famous writer and cultural figure of Uzbekistan Asad Dilmurod (1947-2019).
Keywords: short story; novel; historical truth; artistic interpretation